The Effect of Couple Doping Gd and Co on The Physical Characteristics of LaFeO3 Thick Film for Acetone Gas Sensor Application - Haryadi, Hendi; Syarif, Dani Gustaman; Suhendi, Endi (Universitas Negeri Surabaya, 2022)
The acetone gas sensor is one type of sensor being researched for its application because it detects the presence of diabetes in sufferers. Gas sensors with high sensitivity and low operating temperature have been extensively investigated for this purpose, and this research is focused on the same purpose. Synthetization and characterization of LaFeO3 with co-doping Gd2O3 and CoO thick film ceramics for acetone gas sensor was conducted. LaFeO3 was made using the co-precipitation method with 2.5% CoO for each and 0%, 2.5%, and 5% Gd2O3 variation to the LaFeO3. The LaFeO3 thick film was prepared using the screen-printing technique and calcined at 800°C for two hours. The analysis of crystal structure characterization using X-Ray Diffraction (XRD) resulted in LaFeO3 with co-doping Gd2O3 and CoO thick film ceramics having the same cubic crystal phase with smaller lattice parameters and crystallite sizes after doping were added. The results of morphology structure characterization using Scanning Electron Microscopy (SEM) showed the grain size of the LaFeO3 with co-doping 2.5% CoO and 0%, 2.5%, and 5% Gd2O3 samples to support the analysis of electric property characterization later on. The electric property characterization showed that LaFeO3 with various Gd2O3 concentrations, as part of co-doping with 2.5% CoO, resulted in higher sensitivity compared to the lacking of Gd2O3 one. In order, the maximum sensitivity values of each Gd2O3 concentration are 2.74, 3.06, and 8.76 when exposed to 270 ppm acetone gas at 310°C. Gd2O3, as part of co-doping in LaFeO3 with CoO 2.5%, has successfully increased the sensitivity to the gas sensor yet still can not meet the expectation towards the operating temperature, which is still high compared to other references.